Biomarker panel for early screening of trastuzumab -induced cardiotoxicity among breast cancer patients in west virginia - Pillai, Sneha S.; Pereira, Duane G.; Bonsu, Gloria; Chaudhry, Hibba; Puri, Nitin; Lakhani, Hari Vishal; Tirona, Maria Tria; Sodhi, Komal; Thompson, Ellen (Frontiers in Pharmacology, 2022)
Cardiotoxicity is a well-known pathophysiological consequence in breast cancer patients receiving trastuzumab. Trastuzumab related cardiotoxicity typically results in an overall decline in cardiac function, primarily characterized by reduction in left ventricular ejection fraction (LVEF) and development of symptoms associated with heart failure. Current strategies for the monitoring of cardiac function, during trastuzumab therapy, includes serial echocardiography, which is cost ineffective as well as offers limited specificity, while offering limited potential in monitoring early onset of cardiotoxicity. However, biomarkers have been shown to be aberrant prior to any detectable functional or clinical deficit in cardiac function. Hence, this study aims to develop a panel of novel biomarkers and circulating miRNAs for the early screening of trastuzumab induced cardiotoxicity. Patients with clinical diagnosis of invasive ductal carcinoma were enrolled in the study, with blood specimen collected and echocardiography performed prior to trastuzumab therapy initiation at baseline, 3- and 6-months post trastuzumab therapy. Following 6-months of trastuzumab therapy, about 18% of the subjects developed cardiotoxicity, as defined by reduction in LVEF. Our results showed significant upregulation of biomarkers and circulating miRNAs, specific to cardiac injury and remodeling, at 3- and 6-months post trastuzumab therapy. These biomarkers and circulating miRNAs significantly correlated with the cardiac injury specific markers, troponin I and T. The findings in the present study demonstrates the translational applicability of the proposed biomarker panel in early preclinical diagnosis of trastuzumab induced cardiotoxicity, further allowing management of cardiac function decline and improved health outcomes for breast cancer patients.